Mosque Management as a Reinforcement of Community Religious Moderation - Miyanto, Duwi; Wijaya, Mirza Mahbub; Margiyanti, Dwi Arni Siti (Andragogi: Jurnal Diklat Teknis Pendidikan dan Keagamaan, 2023)
Based on the mosque management strategy, which aims to increase religious activities, we can show the world that we are not allergic to culture and country. The formation of such a mindset can be carried out broadly through good mosque management. This study aims to determine a good direction in increasing religious activities in mosques. This study used a qualitative descriptive method and data collection techniques using observation, interviews, and documentation. The data analysis technique used Creswell's qualitative analysis. In mosque management, which aims to increase religious activities in mosques, several things are found: a) There are values still held by the community from traditions and religious activities in the Baitul Muttaqin mosque. These values include religious values and tolerance values; b) The community views the imam of the mosque as waliyul ilmi forming a moderate and tolerant character in society, while the community views the imam of the mosque from the perspective of da'wah in the form of community empowerment as a form of economic development for the environment, c ) Enculturation carried out by the community around the Baitul Muttaqin mosque in various ways, including through the field of TPQ education, trading in the form of stalls around the mosque, as well as maintaining oral speech which until now has been used in behavior and attitudes determines the good or bad of an Reaction.oral speech which until now has been used in behavior and attitudes determines the good or bad of an action.(Berpijak dari strategi manajemen masjid yang bertujuan untuk meningkatkan kegiatan keagamaan, kita bisa menunjukkan kepada dunia bahwa Islam tidak alergi terhadap budaya dan negara. Pembentukan pola pikir tersebut dapat dilakukan secara luas melalui pengelolaan masjid yang baik. Kajian ini bertujuan untuk mengetahui manajemen yang baik dalam meningkatkan kegiatan keagamaan di masjid. Penelitian ini menggunakan metode deskriptif kualitatif, teknik pengumpulan data menggunakan observasi, wawancara, dan dokumentasi. Teknik analisis data menggunakan analisis kualitatif Creswell. Pada manajemen masjid yang bertujuan untuk meningkatkan kegiatan keagamaan di masjid secara umum dalam pendidikan Islam ditemukan beberapa hal: a) Adanya nilai-nilai yang hingga kini masih dipegang oleh masyarakat dari tradisi dan kegiatan keagamaan di masjid Baitul Muttaqin. Nilai-nilai tersebut diantaranya nilai religi, serta nilai toleransi, b) Perspektif masyarakat terhadap imam masjid dari segi dakwah berupa pemberdayaan masyarakat sebagai wujud pengembangan ekonomi kepada lingkungan, sedangkan perspektif masyarakat terhadap imam masjid sebagai waliyul ilmi membentuk karakter moderat dan toleran di masyarakat, c) Enkulturasi yang dilakukan oleh masyarakat di sekitar masjid Baitul Muttaqin dengan melalui berbagai cara, di antaranya melalui bidang pendidikan TPQ, perdagangan berupa warung di sekitar masjid, serta menjaga ucapan lisan yang hingga kini dijadikan dalam berperilaku dan bersikap menentukan baik buruknya suatu tindakan.)